Dynamic Combination Evaluation Method of Rural Environmental Pollution Control Effect - Xinjie Li (Complexity)
In recent years, the problem of environmental pollution has become more and more serious, and environmental pollution has become a topic of concern. PM2.5, PM10, hazy weather, and other words about environmental pollution have become hot words and topics for the media and the public to talk about, and environmental pollution control is called for by the media and the public. This reflects the rapid development of economy and the obvious changes in people’s living standards, and people have higher requirements and aspirations for their lives and the environment they live in, and their awareness of environmental protection is getting stronger and stronger; however, it also reflects that the rapid development of the economy comes at the cost of damaging the environment. This paper analyzes the current situation and governance dilemma of rural environment by means of field research from dynamic portfolio evaluation theory, explains the problems and causes of environmental pollution management under the requirement of polycentric governance, and proposes countermeasures to solve the problem of environmental pollution management in county. The paper aims to analyze the current state of environmental pollution in rural areas through literature review, villagers’ field interviews, and field research and to explain the application of polycentric governance to rural environmental pollution management in county in the region.